DYNAMICS OF A WOODY COMMUNITY IN A CERRADO sensu stricto AREA IN SPACE AND TIME - Oliveira Silva, Gabriel; Carvalho da Silva, Renata; Bezerra Souza, Flávia; Aurélio Campos Aguiar, Bruno; Cardoso Lopes, Valeria; Bezerra de Souza, Priscila (Floresta, 2022)
The objective of this work was to analyze the changes in the woody community over four years. We established 50 permanent plots of 10 x 10 m where all individuals with breast height circumference above 10 centimeters (CAP ≥ 10 cm) were sampled in 2014 and 2018. In the July 2014 inventory, 2128 individuals belonging to 110 species, 86 genus and 46 families were found, while in the year 2018, 1956 individuals were sampled, distributed in 107 species, 83 genera, and 39 families. In 2014, 66 dead standing individuals were sampled and in 2018, 155 dead individuals were diagnosed. In addition, it was possible to diagnose that in the 2018 survey, seven species were extinct, that is, they were not among the dead standing individuals evaluated in 2014. It is worth noting though that, in the 2018 survey, four new species were included. Thus, it was evaluated that 56 species were able to tolerate the passage of fire with a temperature of approximately 400ºC. The Shannon - Weaver (H') diversity values varied between the two surveys 2014 and 2018, with a value of (3.52) and 2018 (3.61) in 2014. The equability of Pielou (J') in 2014 was 0.79, against 0.77 in 2018, while the Sorensen Index was 0.95 homogeneity between the two surveys 2014/2018. In August 2015 and July 2017, forest fires occurred in the area, which leads to believe that this phenomenon may have been the modulating agent.